A preliminary study of the biologi of tht graáhopper Calliptamus wattenwylianus (orthoptera; Acrididae) - Coca-Abia, M.M.=700 1 Tenas-Perez, I.; Gimenez-Legarre, S.; Garcia-Muñoz, E.
(En, Es)
Ilus., 20 ref
Keywords: CALLIPTAMUS; INSECTOS DAÑINOS; PLAGAS DE PLANTAS; DIAPAUSA; ESPAÑA; SALTAMONTES; ANATREPSIS; CATATREPSIS; BOLETIN DE SANIDAD VEGETAL: PLAGAS